PENGARUH METODE DEMONSTRASI TERHADAP KEMAMPUAN KOGNITIF PADA MATERI IDENTITAS MASYARAKAT DI LINGKUNGAN TEMPAT TINGGALKU - Hertanti, Tri; Mahya Fanny, Arif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using the demonstration method on cognitive abilities on the material of community identity in my neighborhood. This type of research uses quantitative research with a pre-experimental design approach and uses a one group pretest and posttest design. Researchers only use one group as an experimental class. The population in this study were fourth grade students of SDN Balonggarut, Krembung, Sidoarjo, totaling 24 students. The sampling technique used was total sampling, in which all members of the population were involved as samples totaling 24 students. The data collection technique used was a test in the form of a pretest and posttest. Based on the results of the average analysis carried out, there was an increase of 15% from pretest to posttest on questions with analysis indicators (C4). The results of the normality test in this study used Shapiro-Wilk with a pretest value data significance value of 0.141> 0.05 and posttest value data of 0.201> 0.05 so hat the data was normally distributed. The results of the hypothesis test analysis using the paired sample t-test calculation showed a significance value (sig) (2-tailed) of 0.000 <0.05, so H0 was rejected and H1 was accepted. This means that there is an influence from before and after being given treatment in the form of a demonstration learning method on cognitive abilities on the material of community identity in my neighborhood.